(untitled) (Journal of Informatics Education and Research, 2026)
The rapid diffusion of digital technologies has fundamentally altered the structure of modern financial markets. Innovations in financial technology (FinTech), artificial intelligence (AI), blockchain, and clean technology have reshaped how investors access information, evaluate risk, and participate in sustainable investment opportunities. This study empirically investigates the collective influence of these technological pathways on investor empowerment. Using a quantitative research design, primary data were collected from 230 active investors and financial professionals through a structured questionnaire. Reliability and validity of the constructs were examined using Cronbach’s Alpha and Confirmatory Factor Analysis (CFA). Structural Equation Modeling (SEM) via AMOS was employed to test hypothesized relationships. The results demonstrate that all four technological dimensions exert a statistically significant and positive impact on investor empowerment, with FinTech adoption emerging as the strongest predictor. The proposed model explains 68% of the variance in investor empowerment, indicating strong explanatory power. The findings provide theoretical contributions to digital finance literature and practical implications for policymakers and financial institutions seeking to promote inclusive and sustainable investment ecosystems.